항균마감재료와 병원 내 적용 부위 고찰 - 항생제 내성균을 중심으로 - 권순정; 박용현 (의료·복지 건축, 2024)
Purpose: In general, cross-infection caused by bacteria occurs more in hospitals than in local communities. In most cases, infectious diseases spread through contact transmission (direct contact, indirect contact). This study tries to examine which places are most likely to detect infections bacteria and what materials should be used to effectively suppress the spread of infectious bacteria. Methods: Domestic and international literature have been reviewed to determine which bacteria are common and spread in which places. At the same time, antibacterial experiments for several finishing materials are performed to determine the survival period of bacteria for each material. The experiment is conducted mainly on antibiotic-resistant bacteria (MRSA, CRE, etc.) that have a high mortality rate and are very contagious. Results: MRSA has a high incidence in many hospital departments with surgery or immunocompromised patients, such as the elderly, organ transplant patients, and hemodialysis patients. There are experimental results that MRSA dies early in ceramics or silk wallpaper. CRE has a high incidence in hospital departments where there are many patients who are prone to bacteria entering the body directly, such as ventilator patients or critically ill patients with surgical wounds. There are experimental results that CRE dies early in silk wallpaper. In addition, bacteria die on the surface for a variety of reasons. Most MRSA and CRE develop in patients with impaired immunity or surgery, and rapidly die in copper or materials with antibacterial properties. Implications: If finishing materials surface with the ability to kill specific bacteria is used in the place where a large number of specific bacteria are detected, the spread of infectious diseases can be effectively controlled.
Keywords: Interior finishing materials; antibacterial; antibiotic-resistant bacteria; 실내 마감재료; 항균; 항생제 내성균